2010
DOI: 10.1111/j.1365-294x.2010.04757.x
|View full text |Cite
|
Sign up to set email alerts
|

Considering spatial and temporal scale in landscape‐genetic studies of gene flow

Abstract: Landscape features exist at multiple spatial and temporal scales, and these naturally affect spatial genetic structure and our ability to make inferences about gene flow. This article discusses how decisions about sampling of genotypes (including choices about analytical methods and genetic markers) should be driven by the scale of spatial genetic structure, the time frame that landscape features have existed in their current state, and all aspects of a species' life history. Researchers should use caution whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
423
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(437 citation statements)
references
References 99 publications
(102 reference statements)
8
423
2
4
Order By: Relevance
“…Despite the potential implications, the output from functional connectivity analyses is often omitted from conservation plans because they are not carried out in ways that are conducive to management objectives (Keller, Holderegger, van Strien, & Bolliger, 2015). For example, both the spatial extent of the study area and the resolution of landscape variables can influence the estimated importance of landscape features to functional connectivity (Anderson et al., 2010), which makes extrapolation across scales and comparison among studies challenging. Thus, conducting research at scales too large or too small for planning tools will hinder implementation (Keller et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential implications, the output from functional connectivity analyses is often omitted from conservation plans because they are not carried out in ways that are conducive to management objectives (Keller, Holderegger, van Strien, & Bolliger, 2015). For example, both the spatial extent of the study area and the resolution of landscape variables can influence the estimated importance of landscape features to functional connectivity (Anderson et al., 2010), which makes extrapolation across scales and comparison among studies challenging. Thus, conducting research at scales too large or too small for planning tools will hinder implementation (Keller et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2011) found higher correlations between land cover and black bear gene flow in landscapes where forest cover was highly fragmented compared to landscapes of contiguous forest. Yet, the absence of a landscape effect on 2002 SGS may reflect a time lag between when landscape change occurs and when SGS response to landscape change becomes evident (Anderson et al., 2010; Epps & Keyghobadi, 2015). However, when dispersal rates and distances are large, as exhibited in the NLP black bear population (Draheim, 2015; Draheim et al., 2016; Moore et al., 2014), shorter or no time lags are expected (Epps & Keyghobadi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, when dispersal rates and distances are large, as exhibited in the NLP black bear population (Draheim, 2015; Draheim et al., 2016; Moore et al., 2014), shorter or no time lags are expected (Epps & Keyghobadi, 2015). Also, legacy effects of historical landscape processes may be reduced using genetic markers with higher mutations rates (i.e., microsatellites) that reach mutation–drift equilibrium quickly and genetic measures that respond rapidly to changes in connectivity (e.g., Dps) (Anderson et al., 2010). A number of simulation studies have found landscape effects on SGS could be detected with relatively short time spans (Cushman & Landguth, 2010; Landguth et al., 2010; Murphy, Evans, Cushman, & Storfer, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations